Heavy metal accumulation in leaves affects physiological performance and litter quality of Quercus ilex L. - Maisto, Giulia; Santorufo, Lucia; Arena, Carmen (JOURNAL OF PLANT NUTRITION AND SOIL SCIENCE, 2013)
This study aimed to investigate the relationships between leaf functional modifications and heavy metal concentrations of Quercus ilex L., a good bioindicator of air quality. In addition, as metal concentration in litter plays an important role in decomposition and, in turn, in biogeochemical cycles, samples of undecomposed and whole-leaf litter were analyzed for heavy metals. Leaves and leaf litter of Q. ilex were collected at six sites (roadsides, motorway sites, and urban parks) in Naples (Southern Italy) and characterized for Cd, Cr, Cu, Ni, and Pb concentrations. The investigated functional leaf traits were: leaf area (LA), specific leaf area (SLA), leaf dry-matter content (LDMC), water content (WC), leaf relative water content (RWC), maximal PSII photochemical efficiency (F-v/F-m, variable fluorescence / maximal fluorescence), and total chlorophyll concentration. The motorways were the most contaminated sites, and Pb was the main responsible source of contamination. The metal contamination caused slight variation of F-v/F-m, suggesting that metals did not significantly alter functionality of the photosynthetic apparatus. On the other hand, it can be supposed that higher leaf deposit can cause an increase of pigment biosynthesis in response to the shading increase caused by dust deposition.
Keywords: Bioindicator; heavy metal contamination; leaf traits; maximum PSII photochemical efficiency; Urban environment

Seasonal physiological responses of Argania spinosa tree from Mediterranean to semi-arid climate - Díaz-Barradas, Mari Cruz; Zunzunegui, María; Ain-Lhout, Fatima; Jáuregui, Juan; Boutaleb, Said; Álvarez-Cansino, Leonor; Esquivias, Mari Paz (Plant and Soil, 2010)
Argania spinosa (the argan tree) is a slowgrowing tree endemic of Morocco, growing on semiarid areas where no other tree species can live. With the aim of predicting temporal changes in A. spinosa woodlands under a probable increase in aridity, we set off to investigate these questions: how do A. spinosa physiological attributes respond to variations in climatic conditions and seasonality, and which is the set of attributes that most affects tree response to environmental conditions? In three study sites, Beni Snassen (North), High-Atlas (Mountain) and Admine Forest in Agadir (Coastal), gas exchange measurements, photochemical efficiency, leaf water potential and different leaf attributes were monitored in February, July and November of 2006. The Mountain site presents the most continental climate. Trees in this site were the most stressed in summer, having the lowest midday leaf water potential values, photochemical efficiency and assimilation rates. We found a Ψmd threshold around -4 MPa, below which stomatal conductance responds linearly to Ψmd . Plants from the North area never reached this threshold during the study period. Although leaf pigments presented a clear seasonal pattern, leaves from Coastal trees exhibit the highest content for each season. The three study sites were separated by two discriminate functions obtained by canonical discriminant analysis. In summer, the Mountain population is separated from the other sites mainly by assimilation rate and Fv /Fm, while in winter transpiration rates and chlorophyll content are the main discriminant variables. Our study shows that A. spinosa trees adjust their physiological status and leaf attributes to environmental conditions allowing plants to thrive under a dry climate. Under a scenario of global change, the distribution of the argan tree likely shifts to milder areas.
Keywords: Browsing; Drought; leaf traits; photochemical efficiency; Stomatal conductance; water relations

Seasonal variability of dry matter content and its relationship with shoot growth and nonstructural carbohydrates - Palacio, Sara; Milla, Rubén; Albuixech, Jorge; Pérez-Rontomé, Carmen; Camarero, Jesús Julio; Maestro, Melchor; Montserrat-Martí, Gabriel (New Phytologist, 2008)
* • This study assesses how different phases of shoot growth underlie seasonal change in leaf and stem dry matter content (LDMC and SDMC, respectively) of 12 woody Mediterranean species. The relationship between LDMC and nonstructural carbohydrate (NSC) concentrations is also explored and the seasonal vs interspecies variability of LDMC compared. * • LDMC, SDMC and shoot elongation rate (SER) were measured on a monthly basis for a minimum of 12 months. Bud growth rate (BGR) and NSC concentrations were also assessed in several of the study species. * • LDMC and SDMC decreased during shoot elongation in spring and increased in summer, showing a significant negative correlation with SER, but were unrelated to BGR. Half of the species analysed showed a positive relationship between LDMC and NSC. Seasonal fluctuations of LDMC within species were higher than interspecies differences, and species ranking was significantly affected by the month of sampling, except during winter months. * • Seasonal changes in LDMC and SDMC are mainly related to shoot elongation phenology, and NSC sink–source relationships between old and growing organs can explain this relationship in some species. Owing to the high seasonal variability in LDMC, it is recommended that samples for comparative purposes should be collected as close to the winter as possible.
Keywords: Carbohydrate Metabolism; functional classifications; leaf dry matter content (LDMC); leaf traits; leaf water status; Mediterranean; Phenology; Plant Development; Plant Leaves; Plant Leaves: growth & development; Plant Leaves: metabolism; Plant Shoots; Plant Shoots: growth & development; Plant Shoots: metabolism; Plant Stems; Plant Stems: growth & development; Plant Stems: metabolism; Plants; Plants: metabolism; Seasons; shoot growth; Species Specificity

Seasonal variability of dry matter content and its relationship with shoot growth and nonstructural carbohydrates - Palacio, Sara; Milla, Rubén; Albuixech, Jorge; Pérez-Rontomé, Carmen; Camarero, Jesús Julio; Maestro, Melchor; Montserrat-Martí, Gabriel (New Phytologist, 2008)
* • This study assesses how different phases of shoot growth underlie seasonal change in leaf and stem dry matter content (LDMC and SDMC, respectively) of 12 woody Mediterranean species. The relationship between LDMC and nonstructural carbohydrate (NSC) concentrations is also explored and the seasonal vs interspecies variability of LDMC compared. * • LDMC, SDMC and shoot elongation rate (SER) were measured on a monthly basis for a minimum of 12 months. Bud growth rate (BGR) and NSC concentrations were also assessed in several of the study species. * • LDMC and SDMC decreased during shoot elongation in spring and increased in summer, showing a significant negative correlation with SER, but were unrelated to BGR. Half of the species analysed showed a positive relationship between LDMC and NSC. Seasonal fluctuations of LDMC within species were higher than interspecies differences, and species ranking was significantly affected by the month of sampling, except during winter months. * • Seasonal changes in LDMC and SDMC are mainly related to shoot elongation phenology, and NSC sink–source relationships between old and growing organs can explain this relationship in some species. Owing to the high seasonal variability in LDMC, it is recommended that samples for comparative purposes should be collected as close to the winter as possible.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd accession-num: 18643937
Keywords: Carbohydrate Metabolism; functional classifications; leaf dry matter content (LDMC); leaf traits; leaf water status; Mediterranean; Phenology; Plant Development; Plant Leaves; Plant Leaves: growth & development; Plant Leaves: metabolism; Plant Shoots; Plant Shoots: growth & development; Plant Shoots: metabolism; Plant Stems; Plant Stems: growth & development; Plant Stems: metabolism; Plants; Plants: metabolism; Seasons; shoot growth; Species Specificity